Multiprobe high-pressure experiments in CePd0.6Rh0.4 and CePd3 - Pedrazzini, P.; Jaccard, D.; Deppe, M.; Geibel, C.; Sereni, J.G.; Sereni, Julián; Pedrazzini, Pablo (Elsevier, 2009)
Fil: Pedrazzini, P. Comisión Nacional de Energía Atómica. Instituto Balseiro, Argentina; University of Geneva; Suiza